The Bioactive Phenolic Agents Diaryl Ether CVB2-61 and Diarylheptanoid CVB4-57 as Connexin Hemichannel Blockers - Anne Dierks; Corinne Vanucci-Bacqué; Anne-Marie Schäfer; Tina Lehrich; Frederike Ruhe; Patrik Schadzek; Florence Bedos-Belval; Anaclet Ngezahayo (MDPI AG, 2022)
Inflammation mediators enhance the activity of connexin (Cx) hemichannels, especially in the epithelial and endothelial tissues. As potential release routes for injury signals, such as (oligo)nucleotides, Cx hemichannels may contribute to long-lasting inflammation. Specific inhibition of Cx hemichannels may therefore be a mode of prevention and treatment of long-lasting, chronic sterile inflammation. The activity of Cx hemichannels was analysed in N2A and HeLa cells transfected with human Cx26 and Cx46 as well as in Calu-3 cells, using dye uptake as functional assay. Moreover, the possible impacts of the bioactive phenolic agents CVB2-61 and CVB4-57 on the barrier function of epithelial cells was analysed using Calu-3 cells. Both agents inhibited the dye uptake in N2A cells expressing Cx26 (>5 µM) and Cx46 (>20 µM). In Calu-3 cells, CVB2-61 and CVB4-57 reversibly inhibited the dye uptake at concentrations as low as 5 µM, without affecting the gap junction communication and barrier function, even at concentrations of 20 µM. While CVB2-61 or CVB4-57 maintained a reduced dye uptake in Calu-3 cells, an enhancement of the dye uptake in response to the stimulation of adenosine signalling was still observed after removal of the agents. The report shows that CVB2-61 and CVB4-57 reversibly block Cx hemichannels. Deciphering the mechanisms of the interactions of these agents with Cx hemichannels could allow further development of phenolic compounds to target Cx hemichannels for better and safer treatment of pathologies that involve Cx hemichannels.